Strategi peningkatan inklusivitas ekonomi: Analisis perkembangan UMKM pentol kabul melalui perilaku pembelian impulsif di pasar yang kompetitif di Kabupaten Mojokerto - Aini, Adinda Putri Nur (Maliki Interdisciplinary Journal, 2024)
Several strategic considerations led to the founding of the "Pentol Kabul" company in Mojokerto, which furthers the company’s prosperity and significance in the area. These elements consist of the presence of a possible regional market, the accessibility of sufficient raw materials, The MSME sector is expanding quickly, and there are strong partnerships with the community. regional. The choice to operate in Mojokerto was made after considering market demands, resource availability, and the possibility of long-term growth. Pentol Kabul works as a home business that Mr. Slamet founded in Mojokerto. This company has inspired the achievement of Pak Slamet to extend an invitation to join and settle there. Considered the Mojokerto region’s hub for the production of Kabul bulbs. Examination of the situation.